OXA1L mutations cause mitochondrial encephalopathy and a combined oxidative phosphorylation defect. Issue 11 (10th September 2018) - Thompson, Kyle; Mai, Nicole; Oláhová, Monika; Scialó, Filippo; Formosa, Luke E; Stroud, David A; Garrett, Madeleine; Lax, Nichola Z; Robertson, Fiona M; Jou, Cristina; Nascimento, Andres; Ortez, Carlos; et al.
Abstract: OXA1, the mitochondrial member of the YidC/Alb3/Oxa1 membrane protein insertase family, is required for the assembly of oxidative phosphorylation complexes IV and V in yeast. However, depletion of human OXA1 (OXA1L) was previously reported to impair assembly of complexes I and V only. We report a patient presenting with severe encephalopathy, hypotonia and developmental delay who died at 5 years showing complex IV deficiency in skeletal muscle. Whole exome sequencing identified biallelic OXA1L variants (c.500_507dup, p.(Ser170Glnfs*18) and c.620G>T, p.(Cys207Phe)) that segregated with disease. Patient muscle and fibroblasts showed decreased OXA1L and subunits of complexes IV and V. Crucially, expression of wild‐type human OXA1L in patient fibroblasts rescued the complex IV and V defects. Targeted depletion of OXA1L in human cells or Drosophila melanogaster caused defects in the assembly of complexes I, IV and V, consistent with patient data. Immunoprecipitation of OXA1L revealed the enrichment of mtDNA‐encoded subunits of complexes I, IV and V. Our data verify the pathogenicity of these OXA1L variants and demonstrate that OXA1L is required for the assembly of multiple respiratory chain complexes. Synopsis: This work describes the first confirmed pathogenic variants in OXA1L in a mitochondrial disease patient with tissue‐specific combined OXPHOS deficiencies. OXA1L was shown to be important for complex IV assembly in human cell lines with targeted depletion of OXA1L and in patient tissues. Bi‐allelic variants in OXA1L (NM_005015.3; c.500_507dup, p.(Ser170Glnfs*18); c.620G>T, p.(Cys207Phe) were identified by whole exome sequencing in a patient with hypotonia, developmental delay and severe encephalopathy who died following cardiorespiratory arrest. Patient fibroblasts showed decreased protein levels of OXA1L and subunits of OXPHOS complexes I, IV and V. Introduction of wild‐type OXA1L into patient fibroblasts by retroviral transduction rescued the OXPHOS defects, confirming pathogenicity of the OXA1L variants. Depletion of OXA1L by siRNA in human cell lines and Drosophila caused combined OXPHOS deficiencies including severe effects on complex IV. An OXA1L CRISPR/Cas9 knockout cell line with inducible expression of FLAG‐tagged OXA1L was used for OXA1L immunoprecipitation and identified an enrichment of mtDNA‐encoded subunits of complexes I, IV and V. Abstract : This work describes the first confirmed pathogenic variants in OXA1L in a mitochondrial disease patient with tissue specific combined OXPHOS deficiencies. OXA1L was shown to be important for complex IV assembly in human cell lines with targeted depletion of OXA1L and in patient tissues.